308Cardiac fibroblasts as inflammatory supporter cells trigger cardiac inflammation in heart failure. (15th July 2014) - Lindner, D; Zietsch, C; Fluschnik, N; Blankenberg, S; Schultheiss, HP; Tschoepe, C; Westermann, D
Abstract: Purpose: Cardiac remodeling and inflammation are hallmarks of cardiac failure and correlate with outcome in patients. However, the basis for the development of both remains unclear. We have previously reported that cardiac inflammation triggers transdifferentiation of fibroblasts to myofibroblasts and therefore increase accumulation of cardiac collagen deposition, one key pathology in cardiac remodeling. Identifying key pathways in inflammation would therefore be beneficial for patients suffering from heart failure. Here, we investigate the role of fibroblasts in the inflammatory process. Methods and Results: We address for the first time the role of fibroblasts as inflammatory supporter cells in heart failure. Using endomyocardial biopsies from patients with heart failure and dilated cardiomyopathy, we created a primary human cardiac fibroblasts cell culture system. To stimulate the primary fibroblasts we used the flexercell system with increasing stretch intensities. We found that mechanical stretch mimicking cardiac dilation in heart failure induce activation of fibroblasts and not only stimulates production of extracellular matrix but more importantly up-regulates chemokine production and triggers typical inflammatory pathways in vitro. Furthermore different pathways inhibitors were used to determine the signaling pathway involved in the chemokine production induced by mechanical stretch. Moreover, the cell culture supernatant of stretched fibroblasts activates inflammatory cells and induces further recruitment of monocytes by allowing transendothelial migration into the cardiac tissue. Experiments with other cardiac cells exposed to mechanical stretch revealed that the induction of chemokine expression by mechanical stretch seems to be specific for fibroblasts. Conclusion: Our findings reveal that cardiac fibroblasts are chemoactive sentinel cells activated by mechanical stress and are able to recruit inflammatory cells into the cardiac tissue, a process known to aggravate prognosis of patients. This might be important in different forms of heart failure and therefore may be one general mechanism specific for fibroblasts.